Enhancing academic engagement through students’ perceptions of teacher expectations: the mediating role of intentional self-regulation in middle school - Wang, Haiying; Sun, Yueyang; Zhao, Xin; Wang, Weichen; Xue, Jie (Frontiers in Psychology, 2024)
In the context of evolving educational standards, enhancing students’ academic engagement has emerged as a critical factor in mitigating the risks of school aversion among middle school students. This study examines the longitudinal effect of middle school students’ perceptions of teacher expectations on their academic engagement, as well as the mediating role of intentional self-regulation in this dynamic. A six-month longitudinal survey was conducted with 702 Chinese middle school students through three waves of questionnaires. The results showed that students’ perception of teacher expectations significantly predicted their academic engagement, with higher perceived teacher expectations leading to increased academic engagement. Furthermore, the study revealed that intentional self-regulation played a pivotal mediating role in the relationship between students’ perceptions of teacher expectations and academic engagement. Students’ perceptions of teacher expectations at Time 1 positively influenced their intentional self-regulation at Time 2, which subsequently enhanced their academic engagement at Time 3. These findings highlight the crucial impact students’ perceptions of teacher expectation on adolescents’ academic motivation and provide guidance for educators to implement proactive strategies that enhance students’ academic development.